KEBUTUHAN MESIN PERTANIAN DAN TENAGA UNTUK MEKANISASI USAHATANI PADI SKALA KECIL DI KABUPATEN KAMPAR, PROVINSI RIAU - Ujang Paman; Khairizal Khairizal; Hajry Arief Wahyudy (DINAMIKA PERTANIAN, 2017)
Farm machinery is one of the important power sources to carry out farm operations today. The availability of farm power in adequate number is prerequisites for providing enough power in perform rice farming operation. This paper attempts to evaluate the farm machinery and power requirement for performing operations of small-scale rice farming in Kampar Regency, Riau Province. Data were obtained from field survey in 15 districts from 21 districts of Kampar Regency. Village surveys were chose for each selected district which are rice production center and farm machines have been used in working rice farm operations. Samples were purposively selected and consisted of 30 farmers, 5 extension staffs and 20 machine operators. They were interviewed to collect field data on September 2015 by using questionnaires. The results show that the number of farm machinery was not sufficient to fulfill requirement and provide enough power for farm operations. From farm machinery available, it provided power about 0.61 hp.ha-1, while minimum power required for efficient rice farming is about 0.8 hp.ha-1. The results suggest that the number and type of farm machinery must be increased with financial support and involve private sectors.